Determinant of Unemployment Duration with Survival Analysis - Safitri, Hendri Cahyo Dwi; Afiatno, Bambang Eko (Universitas Gorontalo, 2020)
This study aims to analyze the duration of unemployment in Gorontalo Province. The data used in the form of secondary data came from the National Labor Force Survey (Sakernas) in August 2018. The data source was obtained from the Statistics Indonesia (BPS). The total observation units used in this study were 707 individuals consisting of 122 censored data and 585 uncensored data. The technical analysis used in this study is survival analysis. The results showed that on average, the duration of unemployment in Gorontalo Province was 3.8 months. From the results of testing the variables that are significant to the duration of unemployment in Gorontalo Province, namely: sex, education level, and classification of residential areas.